2011
DOI: 10.1108/01409171111146661
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of ocean container carrier selection criteria: an Indian shipper's perspective

Abstract: PurposeThe purpose of this paper is to assist ocean container carriers in devising effective marketing strategies to attract and retain Indian shippers by letting them understand the list of criteria Indian shippers use in the carrier selection decisions and also the amount of importance they assign to each criterion during such decisions.Design/methodology/approachTo explore the criteria, review of transportation literature, customer satisfaction survey questionnaires of container carriers and SERVQUAL batter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 20 publications
(31 reference statements)
1
38
0
1
Order By: Relevance
“…Joo et al (2017) developed a framework for benchmarking freight rates and identified the causes of different shipping cost for shippers and their transport outsourcing strategies. Kannan et al (2011) studied the factors governing the selection criterion for carriers from the Indian market. Authors identified first and foremost "low freight" with the following of "pricing flexibility" is the second ranked one.…”
Section: Transport Costmentioning
confidence: 99%
See 1 more Smart Citation
“…Joo et al (2017) developed a framework for benchmarking freight rates and identified the causes of different shipping cost for shippers and their transport outsourcing strategies. Kannan et al (2011) studied the factors governing the selection criterion for carriers from the Indian market. Authors identified first and foremost "low freight" with the following of "pricing flexibility" is the second ranked one.…”
Section: Transport Costmentioning
confidence: 99%
“…For example, Setamanit and Pipatwattana (2015) emphasized that freight carrier selection criteria are very vital to deliver best services to the customer in Thailand. Similarly, Kannan et al (2011) have examined and classified the significant criteria for shipping carrier selection in Indian perspective, and Shen et al (2015) studied the factors governing the selection criterion for carriers in the Chinese market. This research is important concerning rules regulations, environmental policies, and economic trends explicitly in Pakistan, hence it is of high significance that we understand the selection criteria of shipping lines locally in Pakistan as well and how shipping lines can serve their customers competently.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have identified service quality as the important factor observed by the transport service buyers when buying transport services from the carriers [22,28,37].…”
mentioning
confidence: 99%
“…Reliability in delivery was identified as the important by the shippers when making choice of ocean carrier [12,15,35,36]. Kannan, Bose and Kannan [37] applied the AHP to evaluate the ocean container carriers' selection criteria and found that low freight was ranked as the most important selection criteria by the shippers.…”
mentioning
confidence: 99%
See 1 more Smart Citation